Screening and identification of plasma lncRNAs uc.48+ and NR_105053 as potential novel biomarkers for cured pulmonary tuberculosis. (March 2020) - Li, Zhi-Bin; Han, Yu-Shuai; Wei, Li-Liang; Shi, Li-Ying; Yi, Wen-Jing; Chen, Jing; Huang, Huai; Jiang, Ting-Ting; Li, Ji-Cheng
Graphical abstract: Highlights: This study is the first to screen the potential lncRNA biomarkers for cured tuberculosis (TB) in human plasma. Two lncRNAs were identified as potential novel biomarkers for cured TB. A cured TB model was established with an AUC (area under the curve) of 0.945. Three target genes of the two lncRNAs were predicted. The new strategy provided in this study is different from the existing bacterial tests. Abstract: Background: Tuberculosis (TB) treatment takes a long time, and a gold standard test to define TB cure is lacking. This may lead to early discharge of TB patients, resulting in an increased risk of disease transmission and drug resistance. Plasma lncRNAs might act as potential biomarkers to evaluate TB cure in an efficient and precise manner. Methods: A lncRNA microarray assay was used to screen differentially expressed plasma lncRNAs in untreated TB and cured TB subjects. The expression levels of lncRNAs were verified by qPCR. Target genes of lncRNAs were predicted using a coding–non-coding gene co-expression network and mRNA–lncRNA–miRNA interaction network analysis. Results: The expression levels of lncRNAs uc.48+ ( p < 0.001) and NR_105053 ( p = 0.03) were found to differ significantly between the untreated TB group and the cured TB group. The predicted target genes of uc.48+ were EP300, BAI1 and NR_105053 were TLR9, MYD88, BAI1, respectively. A predictive model for cured TB was established by the combination of uc.48+ and NR_105053 expression, with a sensitivity of 90.00% and specificity of 86.36%, and an area under the curve (AUC) value of 0.945. Conclusions: lncRNAs uc.48+ and NR_105053 may serve as potential biomarkers to distinguish between untreated TB patients and cured TB subjects. This study provides an experimental basis to evaluate the effect of TB treatment and may also provide new clues to the pathological mechanisms of TB.